Future projections of the prevalence of dementia in Japan: results from the Toyama Dementia Survey - Nakahori, Nobue; Sekine, Michikazu; Yamada, Masaaki; Tatsuse, Takashi; Kido, Hideki; Suzuki, Michio (BMC geriatrics, 2021)
This study aimed to make future projections of the nationwide prevalence of dementia in Japan using the prevalence of dementia from the Toyama Dementia Survey and population projections. We performed linear regression analysis using the prevalence of dementia by sex and age in 1985, 1990, 1996, 2001, and 2014 from the Toyama Dementia Survey to calculate the estimated future prevalence by sex and age. The estimated prevalence was then multiplied by the estimated future population of people aged 65 years and older by sex and age in each of the 47 prefectures from 2020 to 2045 and added together to calculate the total number of people with dementia. The estimated future prevalence of dementia was calculated by dividing the calculated number of people with dementia by the estimated future population of people aged 65 years and older in each of the 47 prefectures. In addition, the estimated future prevalence of dementia in each of the 47 prefectures from 2020 to 2045 was presented on a map of Japan and grayscale-coded in four levels. In 2020, the estimated future prevalence of dementia did not exceed 20% in any prefecture, but in 2025, five prefectures, mainly rural prefectures, had projected rates exceeding 20%. In 2030, the prevalence rate is projected to exceed 20% nationwide, and by 2035, the rate will exceed 25% in 42 prefectures. In 2045, all prefectures excluding Tokyo are projected to have a dementia prevalence rate exceeding 25%, and the rate will exceed 30% in 12 of 47 prefectures. Over the next 25 years, the prevalence of dementia in people older than 65 years is projected to exceed 25% nationwide, including metropolitan areas.